2015
DOI: 10.1093/icesjms/fsv109
|View full text |Cite
|
Sign up to set email alerts
|

Eastern Baltic cod in distress: biological changes and challenges for stock assessment

Abstract: The eastern Baltic (EB) cod (Gadus morhua) stock was depleted and overexploited for decades until the mid-2000s, when fishing mortality rapidly declined and biomass started to increase, as shown by stock assessments. These positive developments were partly assigned to effective management measures, and the EB cod was considered one of the most successful stock recoveries in recent times. In contrast to this optimistic view, the analytical stock assessment failed in 2014, leaving the present stock status unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(133 citation statements)
references
References 46 publications
5
127
1
Order By: Relevance
“…The finding that smaller cod remain uninfected or merely lightly infected until they reach a TL of 30 cm may have implications for the ecology of this fish species in the eastern Baltic Sea. During the last decade, a high survival rate and increasing numbers have been recorded for small cod (TL < 30 cm) whereas the population of larger cod (TL > 38 cm) has exhibited a drastic and unexpected decline (Eero et al 2015). Direct predation on cod by seals has been suggested to have caused a reduction in Canadian fish stocks (Chouinard et al 2005, Swain & Chouinard 2008, Swain & Benoit 2015, and predation may play a role for the Baltic cod as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that smaller cod remain uninfected or merely lightly infected until they reach a TL of 30 cm may have implications for the ecology of this fish species in the eastern Baltic Sea. During the last decade, a high survival rate and increasing numbers have been recorded for small cod (TL < 30 cm) whereas the population of larger cod (TL > 38 cm) has exhibited a drastic and unexpected decline (Eero et al 2015). Direct predation on cod by seals has been suggested to have caused a reduction in Canadian fish stocks (Chouinard et al 2005, Swain & Chouinard 2008, Swain & Benoit 2015, and predation may play a role for the Baltic cod as well.…”
Section: Discussionmentioning
confidence: 99%
“…These pinnipeds are final hosts for both C. osculatum and P. decipiens (Marcogliese et al 1996, McClelland 2002, Mattiucci & Nascetti 2008, Skrzypczak et al 2014, Lunneryd et al 2015. Eero et al (2015) suggested that heavy C. osculatum liver infections may partly explain the distress of the eastern population of Baltic cod, where juveniles (< 30 cm total length [TL]) perform successfully but larger cod (> 38 cm TL) show increased mortality. However, so far no parasitological studies on the infection of juvenile stages of Baltic cod are available, and it is therefore important to address this question.…”
Section: Introductionmentioning
confidence: 99%
“…F MSY was estimated as the fishing mortality, with a given fishing pattern, that gives the longterm maximum yield. The definition of stock targets turned difficult in 2014, due to a regime shift in the Baltic ecosystem (Möllmann et al, 2009) in combination with input data quality concerns (Eero et al, 2015). Because of that, advice on harvest opportunities is recently based on a combined biomass index from two surveys, used as proxy for spawning stock biomass (ICES, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…An example of this was the case of the Eastern Baltic cod stock in 2014 when an ICES assessment failed to provide adequate feedback on the present stock of cod (cf. Eero et al 2015 ). The uncertainty challenge has therefore been and is still high on the agenda of both scientists and politicians, particularly because the TAC system in general has not been able to resolve the problems of overfi shing and resource depletion Villasante et al 2011).…”
Section: Uncertainty As a Key Challengementioning
confidence: 99%
“…Epistemic uncertainty on the other hand stems from a lack of knowledge of dynamics or phenomena within the fi eld. Although extended data gathering and research might decrease both aleatory and epistemic uncertainties, with dynamic systems such as marine environments, uncertainty often prevails and can even increase as a consequence of further research as it happened in 2014 with the failure of ICES' Eastern Baltic cod assessment (Eero et al 2015 ).…”
Section: Dealing With Uncertainty In Assessment-management Interactionsmentioning
confidence: 99%